Pengaruh Variasi Sudut Kemiringan Instalasi Soil Nailing pada Perkuatan Lereng - Rafiansyah, Rafli Rizki; Resdiana, Rafli Aridzalrahman; Ardadinata, Raihan; Rizkyanto, Dheva Ferdinand; Sulaeman, Agus (Universitas Batanghari Jambi, 2025)
Slope stability is a critical aspect in the planning and implementation of construction projects in contoured or sloped areas. One commonly used reinforcement method is soil nailing, which involves the passive installation of steel bars to increase slope resistance against lateral earth pressure. This study aims to analyze the effect of nail installation angle variation on slope stability parameters under two slope conditions, namely 27° , 35° and 45°. The simulation was carried out using PLAXIS 2D version 2024, with nail angles ranging from 10° to 90°. The parameters analyzed include safety factor, maximum horizontal deformation, horizontal effective stress, and bending moment in the nail elements. The simulation results show that lower installation angles, around 10° to 25° provide the most optimal performance in terms of safety improvement, reduced deformation, stable stress distribution, and efficient structural response. The steeper slope (35°) generally produced higher deformation, stress, and bending moment values compared to the 27° slope, indicating that steeper slopes impose greater internal loads on the reinforcement system.